"Flint Can't Get in the Hearing": The Language of Urban Pathology in Coverage of an American Public Health Crisis. (January 2020) - Carey, Michael Clay; Lichtenwalter, Jim
This study examines the presence and influence of urban pathology language in coverage of the Flint, Michigan, water crisis. The use of urban pathology language to describe low-income urban neighborhoods may lead news consumers to "understand those communities entirely in terms of their problems." This study of coverage in The New York Times and the Wall Street Journal describes urban pathology frames that suggest a lack of agency among residents. The use of those frames, the study argues, may distract from broader questions of environmental justice.